Virtual Reality In Increasing Readiness For Childbirth: Literature Review: Persiapan Persalinan Dengan Virtual Reality: Literature Review - Chairunisa, Navira; Sukihananto, Sukihananto (Politeknik Kesehatan Kemenkes RI Jakarta I, 2024)
Virtual reality (VR) is used as a new technology to enhance the readiness of pregnant women for childbirth to reduce pain and anxiety. This literature review explores the effectiveness of virtual reality (VR) and augmented reality (AR) for pregnant women in preparing for childbirth. The research uses a literature review method. The data used comes from PubMed, Scopus, Science Direct, EBSCO, PROQUEST, and Google Scholar with several keywords: anxiety, pregnancy, and virtual reality. The inclusion criteria for international journals published from 2013 to 2022. The research topic is the utilization of VR methods in passive forms such as pre-recorded VR videos displayed on a screen. The exclusion criteria established are articles that cannot be accessed in full text and review articles. There are twelve journals were selected. All provided VR interventions for exercise simulations during pregnancy and diet simulations for pregnant women with gestational diabetes, one pilot study, and one literature review study to evaluate the effectiveness of VR on pain and anxiety before childbirth, using various types of VR. The conclusion is the application of virtual reality has a positive impact on reducing anxiety, increasing satisfaction, and improving pain management during labor compared to other groups with standard care. VR can help pregnant women prepare emotionally for childbirth. The recommendation for next studies on virtual reality be conducted to be applied as an intervention for pregnant women, especially for childbirth preparation in Indonesia.